Production performance of backyard chicken under the care of women in Charsadda, Pakistan - Farooq, M.; Gul, N.; Chand, N.; Durrani, F.R.; Khurshid, A.; Ahmed, J.; Asghar, A.; Zahir-ud-Din. (2002)
Information from 400 randomly selected female farmers was obtained during the year 1997 to assess the production performance of backyard chicken in Charsadda district, North West Frontier Province (NWFP), Pakistan. Only 16.3% of the farmers were regularly vaccinating their flocks. The majority of the farmers initiated immunization only at the time of disease onset (29.7%) followed by those (28.5%) who did not vaccinate. A high proportion (53.3%) provided no housing, 29.8% provide night shelters and 17% had no housing. Average flock size was 22.0 birds, comprising 8.86 chicks, 2.03 pullets and 11.1 layers. The local Desi chicken dominated the flocks (10.2 birds) followed by Fayumi (6.76), Rhode Island Red (4.20) with White Leghorn least popular (0.83 ). Average mortality in a flock was 23.6%. Mortality was higher in layers (28.1%) than in pullets (18.7%) and chicks (24.2%). Significantly higher losses were found in White Leghorn (35.6%) than in Desi chicken (17.5%). Similarly, higher mortality was found in chicken without housing facilities (26.7%) than in those with access to houses (21.6%). Regular vaccination was associated with higher productivity than vaccination at the onset of disease or no vaccination. Average annual egg production was 76.4 for Desi, 109 for Fayumi, 169 for Rhode Island and 153 for White Leghorn. Mean hatchability was 61.2% with an annual frequency of 4.6 settings and 15.1 eggs set per broody hen. Farmer preference for the "local" Desi chicken reflected their greater capacity to survive and adapt to scavenging management systems. Fayumi and Rhode Island chickens appear to merit further studies as breeds that could improve the productivity of scavenging systems, as they had higher egg production and only slightly higher mortality than Desi chicken.